Enhancing Environmental Friendliness through Mobile Phone Learning - Chukwu, M.N (West African Journal of Open and Flexible Learning, 2014)
The study investigated the use of mobile phones to increase apprentices’ use of mobile learning technology and to enhance environmental friendliness. Data were collected from a sample consisting of 30 male automobile apprentices and 30 female hair dressing apprentices in Iwaya community in Lagos using the “usefulness of mobile phone leaming”(UMPL) questionnaire. The apprentices were first trained on how to access text messages, electronic mails, jingles and photographs on mobile phones. This was followed, by a pre-test using the UMPL. The apprentices then voluntarily participated in a four -week programme using mobile phones to send text messages (SMS, MMS), e-mails and jingles warning against environmental pollution. Photographs of local environmental degradation were also transmitted and exchanged. At the end of the programme, a postproject test was conducted also using the UMPL. A paired t-test was used to compare pre-project and post-project means while an independent t-test sample was used to compare pre-project and post-project means between males and females at 0.05 level of significance. The participants learnt various ways of maintaining clean environments which increased their awareness on environmental friendliness. Responses on the questionnaire differ significantly between genders.